The Intersection of Systemic, Child, and Evaluation Factors in the Prediction of Autism Special Education Eligibility; Examining the Role of Race and Ethnicity. - Young, Kelsey; Harris, Bryn; Hall-Lande, Jennifer; Esler, Amy (Journal of Autism & Developmental Disorders, 2024)
Though there is evidence autism identification has been inequitable for populations who are culturally and linguistically minoritized, there is limited research that explains the issue of disproportionality and factors contributing to its occurrence, especially within an educational setting. To explore contributors to racial/ethnic disparities in autism special education eligibility, the current investigation evaluated child and evaluation characteristics as they relate to the absence of autism eligibility. Data were obtained from the Autism and Developmental Disabilities Monitoring (ADDM) Network Study and included children with behavioral characteristics consistent with autism and educational evaluation records. Despite documented characteristics consistent with autism, only 72% of the sample received educational services under autism eligibility. To characterize children without autism eligibility, hierarchical logistic regression was used to evaluate factors documented in evaluation records predicting the absence of autism eligibility. Factors influencing autism eligibility included behavioral characteristics documented, evaluation components completed, intellectual ability, and clinical diagnoses present. There was no unique contribution of race/ethnicity in predicting the absence of autism eligibility when accounting for these previous predictors, but many of these predictors differed by racial/ethnic group. Disproportionality in autism may be the manifestation of inequitable evaluation experiences, including experiencing less comprehensive evaluations, and not receiving an autism specific assessment. Though race/ethnicity did not uniquely contribute to the absence of autism eligibility above and beyond those combined factors, it is important to evaluate and reduce inequities experienced within the autism identification process for populations who are culturally and linguistically minoritized.